Profile of Science Practicum Course, Logical Thinking Ability, and Systems Thinking for Prospective Science Teacher Students in Sorong Regency - Febrian Andi Hidayat; Isnawati Isnawati; Lisa Dewi Ramadany (CV. Dharma Samakta Edukhatulistiwa, 2024)
This research aims to determine the profile of science practicum lectures, logical thinking abilities, and systems thinking skills of prospective science teacher students in Sorong Regency. This research is a case study with pre-research, implementation, and final/post-research stages. The subjects of this research were students who were or had contracted for science practicum course. The instruments used are analysis lists, logical thinking test instruments, systems thinking scales, and systems thinking skills tests. Interviews were also conducted to support the data that had been obtained. The research results show that (1) the practicum activities that have been running so far have only trained skills in collecting, processing, and analyzing scientific research data. (2) The contents of the practicum instructions do not train students' thinking skills, such as critical thinking, systems, or problem-solving. (3) Students' logical thinking abilities are relatively evenly distributed at proportional, correlational, and combinatorial reasoning levels; however, the majority of students have reasoning in the transitional category, and there is quite a high level of concrete reasoning. (4) Students' systems thinking skills are relatively low, especially forest thinking skills. Different and innovative practicum lecture approaches need to be developed to improve logical thinking and systems thinking skills for prospective science teacher students in Sorong Regency. Low levels of logical thinking and systems thinking skills will have implications for achieving skills at the next level, such as the skills needed today, namely 21st-century skills.